1977
DOI: 10.3109/00365527709181339
|View full text |Cite
|
Sign up to set email alerts
|

Liver Histology in a ‘Normal’ Population—Examinations of 503 Consecutive Fatal Traffic Casualties

Abstract: The liver histology of 503 consecutive victims of fatal (within 24 hours) traffic accidents submitted to medico-legal autopsy are used as a standard of reference. In 370 persons (74%) no pathological changes in the liver biopsies were observed. Fatty liver was found in 120 persons (24%), non-specific portal inflammation in 7 persons, alcoholic hepatitis in 6, and portal fibrosis in 5. No cases of cirrhosis, chronic aggressive hepatitis, changes compatible with chronic persistent hepatitis, viral hepatitis, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
113
0
12

Year Published

2003
2003
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(128 citation statements)
references
References 3 publications
3
113
0
12
Order By: Relevance
“…The prevalence of hepatic steatosis in the asymptomatic general population is not well documented in the published literature, with varying results from 3.5% to 24%, as described below (13)(14)(15)(16)(17). Two postmortem studies of random deaths have reported on the prevalence of hepatic steatosis: in a study of 423 aircrew involved in fatal aircraft accidents, 66 cases (15%) had a fatty liver, 11 of which had histopathological evidence of alcohol abuse (14); in a study of 503 fatal road traffic accidents, 24% had a fatty liver and fatty change was significantly correlated with body weight and increasing age (13).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The prevalence of hepatic steatosis in the asymptomatic general population is not well documented in the published literature, with varying results from 3.5% to 24%, as described below (13)(14)(15)(16)(17). Two postmortem studies of random deaths have reported on the prevalence of hepatic steatosis: in a study of 423 aircrew involved in fatal aircraft accidents, 66 cases (15%) had a fatty liver, 11 of which had histopathological evidence of alcohol abuse (14); in a study of 503 fatal road traffic accidents, 24% had a fatty liver and fatty change was significantly correlated with body weight and increasing age (13).…”
Section: Discussionmentioning
confidence: 96%
“…Two postmortem studies of random deaths have reported on the prevalence of hepatic steatosis: in a study of 423 aircrew involved in fatal aircraft accidents, 66 cases (15%) had a fatty liver, 11 of which had histopathological evidence of alcohol abuse (14); in a study of 503 fatal road traffic accidents, 24% had a fatty liver and fatty change was significantly correlated with body weight and increasing age (13). In neither of these studies was detailed information concerning alcohol misuse available.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In random histopathologic studies, the relative proportion of NASH to NAFLD is approximately 1:10. 36,37 This problem has never been systematically evaluated, and selection biases might operate differently in the various series. In the present study, liver biopsy was limited to a subgroup of patients, and it is possible that more severe cases were preferentially selected or gave informed consent to biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD is perhaps the most common of all liver disorders. [17][18][19][20][21][22][23] Wanless and Lentz 24 found steatosis in 70% of obese and 35% of lean patients and NASH in 18.5% of obese and 2.7% of lean patients in a consecutive autopsy study. Among obese patients, the prevalence of class 1 NAFLD (simple steatosis) is about 60%, whereas NASH is found in 20% to 25% and 2% to 3% have cirrhosis.…”
Section: Clinical Aspectsmentioning
confidence: 99%